How maternal age and environmental cues influence embryonic developmental pathways and diapause dynamics in a North American annual killifish. Issue 11 (8th July 2022) - Omar, Domínguez‐Castanedo; Sharon, Valdez‐Carbajal; Alejandra, Martínez‐Blancas; M. Muñoz‐Campos, Tessy
Abstract: Background: Temporary pools are variable environments with seasonal drought/flood phases. Annual killifish have adapted to life in temporary pools by producing embryos that undergo diapause to traverse the dry phase. To fill existing knowledge gaps about embryo diapause regulation and evolution in annual killifishes, we test the effect of maternal age, incubation temperature, and incubation medium on diapause induction and length in Millerichthys robustus, the only North American fish species that has evolved an annual life history. Results: All embryos at extreme temperatures follow a defined developmental pathway: skipping diapause at 30°C, and entering diapause at 18°C, both regardless of maternal age, and incubation medium. However, maternal age, and incubation medium influenced whether diapause is entered, and time arrested in diapause for embryos incubated at 25°C. At 25°C, five‐week‐old, and 52‐week‐old females produced more embryos that entered diapause than 26‐week‐old females. Also, embryos incubated in aqueous medium skipped diapause more frequently at this intermediate temperature. Conclusions: Millerichthys developmental dynamics associated with maternal age under intermediate range of temperatures are likely adapted to the particular patterns of flood/drought in North American temporary pools. Millerichthys also exhibits developmental patterns largely comparable with other annual fishes, probably due to common seasonal patterns in temporary pools. Key Findings: All embryos at extreme temperatures follow a defined developmental pathway, regardless of maternal age. Maternal age, and incubation medium influenced whether diapause is entered, and time arrested in diapause for embryos incubated at 25°C. Embryos incubated in aqueous medium skipped diapause more frequently at this intermediate temperature.